Job alienation of pre-employment contract workers ANEM, ADS - FADEL, Faiza; SAADOUN, Soumia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
This study aimed to identify the level of job alienation among workers of pre-employment contracts by ANEM, ADS agencies in Oran, the descriptive approach was followed to fits with the nature of this study, by applying a questionnaire that was prepared by the researchers of their contact with the field and access to previous studies on the topic, which included 28 items distributed over six (06) dimensions represented by: impotence, meaninglessness, affiliation, non- normality, dissatisfaction and pessimism. Its psychometric properties to verify the linguistic formulation and also relying on the validity of internal consistency by calculating the correlation coefficient between each dimension of the questionnaire with the total score of the questionnaire, and also relying on the Alpha Crombach coefficient to calculate the stability, to be then applied to a sample of 75 pre-employment contracts with ANEM and ADS agencies and the results of the study were analyzed using the appropriate statistical methods (Frequencies, Means, Standard deviation ,independent-samples T test, One-way ANOVA , Pearson Correlation Coefficient, Stability Coefficient Alpha Crombach) based on the SPSS statistical program version 20 and following results were reached: A high level of sense of job alienation has been found in its six dimensions among workers of pre-employment contracts ANEM, ADS in Oran, as well as the absence of statistically significant differences between them in terms of a sense of job alienation depending on the individual variables: gender, age, and agency type.